2006
DOI: 10.1507/endocrj.k06-040
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12B Gene Polymorphism does not Confer Susceptibility to Graves' Ophthalmopathy in Japanese Population

Abstract: Abstract. Graves' disease (GD) is an autoimmune disorder with genetic predisposition and frequently associated with Graves' ophthalmopathy (GO). Interleukin 12 (IL-12) is an important mediator of inflammatory immune responses and is expressed in the thyroid and orbit. IL-12B gene, which encodes the p40 subunit of IL-12, is located at chromosome 5q31-33. The aim of the present study was to investigate whether IL-12B gene polymorphism is associated with the development of GD or GO. IL-12B gene polymorphism was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
1
20
1
Order By: Relevance
“…These results mean that the IL12B gene polymorphism is an unlikely susceptibility factor for Chinese patients with GD. These results are consistent with a previous study (17,20), which suggested that the A/G polymorphism located in the 3 untranslated region of IL12B gene was not associated with Grave's disease. They are also consistent with the data of Walsh et al who found that the MAF for rs6887695 was 0.45 in GD (double that in men with Hashimoto's disease).…”
Section: Discussionsupporting
confidence: 93%
“…These results mean that the IL12B gene polymorphism is an unlikely susceptibility factor for Chinese patients with GD. These results are consistent with a previous study (17,20), which suggested that the A/G polymorphism located in the 3 untranslated region of IL12B gene was not associated with Grave's disease. They are also consistent with the data of Walsh et al who found that the MAF for rs6887695 was 0.45 in GD (double that in men with Hashimoto's disease).…”
Section: Discussionsupporting
confidence: 93%
“…42,43 A previous study in Japan failed to show this association with GD or GO. 13 In contrast, we revealed in an Iranian population a significant increase in the frequency of the 1188C allele and CC genotype among patients with GO. Ethnic differences might explain a part of this inter-population inconsistency.…”
Section: Discussioncontrasting
confidence: 58%
“…10 As proinflammatory cytokines are known to have important roles in the development of GO, 9,11,12 we investigated the hypothesis that specific polymorphisms in proinflammatory cytokine genes might contribute to the development of GO. Previous reports on the topic are limited, [13][14][15][16][17][18][19] and further studies are necessary to elucidate the issue. 20 In this study, the association of GO with the following polymorphisms in proinflammatory cytokines were evaluated in Iranian GD patients with and without GO: IL-12 (À1188A/C), TNF-a (À308A/G, À238A/G), INF-g (UTR 5644A/T), IL-2 (À330T/G, 166G/T), and IL-6 (À174C/G, nt565A/G).…”
Section: Introductionmentioning
confidence: 99%
“…We showed a significant increase in IL-12 -1188C allele and the CC genotype in patients with GD. This association does not seem to be present in Japanese [27,28] and European [29] populations. Our results regarding the association between the C allele and GD are not surprising given that IL-12 levels are elevated in the hyperthyroid phase of GD [27][28][29].…”
Section: Discussionmentioning
confidence: 65%
“…This association does not seem to be present in Japanese [27,28] and European [29] populations. Our results regarding the association between the C allele and GD are not surprising given that IL-12 levels are elevated in the hyperthyroid phase of GD [27][28][29]. IFN-c has a critical role in enhancing the expression HLA class I, class II, and some adhesion molecules on thyrocytes, including intercellular adhesion molecule 1 (ICAM-1) and lymphocyte function-associated antigen-3 (LFA-3).…”
Section: Discussionmentioning
confidence: 65%